Optimization of clay-based ceramic mixtures with sugarcane bagasse fiber for 3D printing - Guilherme Pante Leme de Campos; Pietro Sinigaglia Lunelli; Elisângela Guzi de Moraes; Marcelo Tramontin Souza; Antonio Pedro Novaes de Oliveira (Case Studies in Construction Materials)
Robocasting is an additive manufacturing technique that utilizes a numerically controlled extruder to 3D print objects layer by layer by continuously extruding a paste-like material through a nozzle onto a build surface. This study advances the application of clay-based ceramics for additive manufacturing by optimizing compositions that incorporate sugarcane bagasse fiber, focusing on sustainable materials with minimal environmental impact. Novel combinations of metakaolin, bentonite, and sugarcane bagasse fiber were explored to achieve enhanced printability and mechanical performance. Key innovations include tailoring the liquid-to-solid ratio to achieve optimal plasticity and workability (0.72–0.85) and identifying the critical role of bentonite (≥4 %) in improving the printability of metakaolin with its inherently low plasticity. Additionally, the incorporation of sugarcane bagasse fiber significantly increased compressive strength (by up to 74 %), although it also resulted in a slight increase in shrinkage during drying (13.1 %). This work presents a sustainable and innovative approach for developing printable ceramics with improved properties, supporting the broader adoption of eco-friendly additive manufacturing techniques for high-performance applications.